Successful management of severe pulmonary form of leptospirosis with VV-ECMO, prone ventilation, and bronchoalveolar lavage: two case reports - Chen, Meisong; Wu, Haohao; Xie, Lutao; Wu, Min; Lan, Pin (Frontiers in Medicine, 2025)
BackgroundLeptospirosis is a globally prevalent zoonotic acute infectious disease that can rapidly progress to severe pulmonary form of leptospirosis (SPFL), leading to multiple organ failure with a high mortality rate. It is estimated that approximately 58,900 deaths occur annually due to leptospirosis, with critically ill patients admitted to intensive care units facing extremely high fatality rates. Therefore, timely and effective treatment strategies are crucial.Case presentationTwo patients developed fever after farm work exposure, followed by progressive dyspnea and hemoptysis, leading to hospitalization. They rapidly developed acute respiratory distress syndrome (ARDS) and diffuse alveolar hemorrhage (DAH) with severe thrombocytopenia, accompanied by a continuous decline in the ratio of the partial pressure of arterial oxygen to the fraction of inspired oxygen (PaO₂/FiO₂ [P/F]). Despite endotracheal intubation and mechanical ventilation, hypoxemia persisted. Venovenous extracorporeal membrane oxygenation (VV-ECMO) was initiated to provide oxygenation support, heparin anticoagulation was not used in the early stage. Meanwhile, prone ventilation and bronchoscopy alveolar lavage were performed to promote the clearance of pulmonary hemorrhage, along with anti-infection treatment. The diagnosis of leptospirosis was confirmed through Metagenomic Next-Generation Sequencing (mNGS). Both patients ultimately recovered, were successfully weaned from life support, discharged in stable condition, and returned to normal life.ConclusionEarly VV-ECMO support, combined with prone ventilation and bronchoalveolar lavage, can improve the prognosis of patients with SPFL. mNGS testing aids in the definitive diagnosis of leptospirosis and provides a reliable basis for antibiotic selection.